Community Service Program: Enhancing Church Communication through Website Development Training for GMIM Bait-El Kamasi and Bait-Lahim - Langi, Yohanes Andreas Robert; Mongi, Charles Efraim; Widiana, Siska Ayu; Takaendengan, Mahardika Inra; Lapihu, Dodisutarma (Universitas Teknokrat Indonesia, 2025)
This paper discusses the development and implementation of a website for GMIM Bait-El Kamasi and GMIM Bait-Lahim Talete churches to address communication challenges faced by the congregation. The main problem identified was the reliance on in-person announcements and the unstructured use of social media, which limited access to important church information for members who could not attend services regularly. Based on interviews and surveys, 92% of the congregation expressed the need for a digital platform, with 85% believing it would improve information dissemination and engagement.The solution was to create a user-friendly website that provides real-time updates on worship schedules, announcements, and church activities. Additionally, the website includes a dedicated section for church history and prayer services. Church staff and youth representatives were trained to manage the website, ensuring ongoing content updates and technical maintenance. Regular evaluations will be conducted to assess the website’s effectiveness in improving church communication and participation.This project demonstrates the importance of integrating technology in church operations to enhance engagement and ensure accessibility. The website is expected to have a lasting impact by fostering a more connected church community and addressing the evolving digital needs of its members.